THE IMPACT OF PHYSICAL DISTANCING HEALTH POLICY IN REDUCING COVID-19 INCIDENCE IN THE WORLD IN 2020: LITERATURE REVIEW STUDY - Nurbaiti, Nunik; Ayuningtyas, Dumilah (Journal of Indonesian Health Policy and Administration, 2022)
To reduce and slow the spread of COVID-19, many countries in the world have adopted physical distancing health policy, which have never happened before. This study aims to get an overview of the impact of physical distancing health policy to reduce of COVID-19 incidence in the world at 2020. The research design used was a descriptive qualitative with a narrative literature review method, while the research source came from international journal channels Google Scholar, ProQuest, PubMed, Science Direct, and Scopus with search data for the past five years. The approach used is the input, process, and output (IPO). From the journal search results, there are 10 scientific articles obtained in accordance with the inclusion and exclusion criteria of the search. While the overall results of the study show that the impact of physical distancing health policy can reduce of COVID-19 incidence in the world in 2020. In addition, the decline in the incidence of COVID-19 according to the study is also due to other health interventions carried out simultaneously. The suggestion of this research needs further research with the same topic related to physical distancing health policy. Especially regarding the factors that determine the success of this policy.